Preliminary study site characterization using HVSR microtremor in West Bandung Basin - Fitri Yulianto Gita; Saimima Wakano Qashdina; Widi Santoso Eko; Ridwan Mohamad; Santoso Budy (E3S Web of Conferences)
Site characteristic become crucial factor in seismic hazard assessment correspond to the site response of earthquake motions. This study investigates site characterization in the western part of the Bandung Basin using the Horizontal-to-Vertical Spectral Ratio (HVSR) method. HVSR analysis was applied to the Rayleigh wave microtremor data that was conducted at observation sites i.e: Baros, Cibeber, Batujajar, and Giriasih. The analysis results revealed some soil parameters i.e: dominant period (Td) values ranging from 0.23 to 0.43 seconds, S-wave velocity structure down to a depth of 30 (Vs30) in a range of 173.25 m/s in Cibeber to the highest was 281.76 m/s in Baros. The result of Vs30 analysis were used to classify local site which is Baros site can be classified into the stiff soil (SD) category, Cibeber and Batujajar belong to the soft soil (SC) category, and Giriasih is classified as very soft soil (SE). The findings of this study provide valuable information for seismic hazard assessment, seismic site classification, and earthquake-resistant structural design in the western part of the Bandung Basin.